STRATEGI MENGHIDUPKAN KOTA LAMA SEMARANG (Bagian 01/02) (SUATU KAJIAN PENGARUH IKLIM MIKRO-KENYAMANAN TERMAL-TATA LAMPU PADA TAMAN SRI GUNTING) - Eddy Prianto; Bambang Suyono; Nazaruddin Sinaga; Djaka Windarta (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2017)
Many efforts in reviving the Semarang old city, one of them is holding evening performances. The visitor's comforts are one indicator of the successful arrangement of the old city area, both thermal, visual, and even acoustic comforts. Open space provides a social interaction space. The configuration of the wall in the ancient buildings facades was very appealing to draw people attention. The questions of this study are: How far the role of Sri Gunting park in the old city of Semarang as one of the tourist destinations? How far the role of illumination of the night (especially in the garden) in appealing people to visit? The innovative technology of interdisciplinary lighting arrangement should be designed in taking into account the kind of landscape and morphological characteristics of this ancient area. The methods carried out to answer the above questions are made through questionnaires to respondents (park visitors during the day and night), field observations and measurements of thermal performance and lighting characteristics of the Park. While the discussion is based on an interdisciplinary approach, namely the study of architecture, landscape and lighting layout/lighting/ discipline elekto. The result of the study showed that the existence of Sri Gunting Park is not only presenting the form of green open space element in an ancient building area, but its existence can provide the quality of micro-climate change which makes the sensation level of the visitors' sense of comfort significantly. The role of this region-scale park is potentially adopted on an urban scale. The cultural background of the tourists visiting the old city influenced their perceptions of the buildings and open spaces in the old city presented by successful artificial lighting arrangements. There are two ways to revive the old city of Semarang: Firstly, the success of 'bringing in' the visitors because they feel the thermal and visual comfort sensation. Secondly, the exploitation of artificial lighting at night, either in the park, other open spaces/roads and ancient buildings.